A fully coupled tribo-dynamic model for piston-ring-liner system. (February 2023) - Gao, Lining; Cui, Yi; Xu, Zhaohui; Fu, Yan; Liu, Shuo; Li, Yafen; Hou, Xinrong
Abstract: As key friction pairs affecting the whole engine reliability, the piston-ring-liner system generates more than 45% of the whole engine friction loss. But so far, three-dimensional tribo-dynamic models considering its complex motions are very limited. This paper proposes a new method from the perspective of multi-flexible-body dynamics to realize a fully coupled modeling of the system's deformation, dynamics, and lubrication characteristics. The study considers the ring-groove contact characteristics and calculates the system boundary loads through the blow-by model. The effect mechanism of ring groove deformation on ring properties is revealed, and the system's complex tribo-dynamic behaviors such as twisting and fluttering are characterized. After fully coupled modeling, piston deformation at the ring groove position can be 65.80 µm, resulting in a 1.33 µm reduction in the minimum oil film thickness compared to the uncoupled model, and ring wear unevenness is aggravated. Highlights: Fully coupled modeling of deformation, dynamics, and lubrication characteristics of the piston-ring-liner system. The ring-liner and piston-liner are integrated into a unified model for the simultaneous solution. Piston, ring, and liner are 3D flexible bodies, and the complex ring tribo-dynamic behaviors are characterized in detail. The influence of groove deformation on ring contact state and lubrication performance is considered and analyzed.